PENGEMBANGAN MODUL BERBASIS SAINTIFIK UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS PADA MATERI GERAK HARMONIS DI SMAN BALUNG - Fitria Sulvi Ulandari; Sri Wahyuni; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2018)
AbstractThis research was a development research to produce a development productin the form of scientific based module to train critical thinking ability. 4D was used tobe the development model consisting of 4 stages, but in this research only on untilthird stage that defined, design, and develop. Instrument used in this research wasvalidation sheet, student response questionnaire, and critical thinking ability test.Based on the results of expert validation analysis found that the validity criterion of88.19%, which was at the validity level was very valid and the result of user validationanalysis was known that the validity criteria obtained is 100% and the validity levelwas very valid. The result of pretest and posttest analysis showed that the average NGain score is 0.53 which was in the medium category. Then for the student responseof scientific-based module got a positive response of 88.68%. So the scientific-basedmodule had very practical criteria used in learning.Key word: scientific, validation, student respon, critical thinking.